Community systems strengthening project: the successes and challenges perceived and experienced in Gugulethu, South Africa - Mautsa, Tafadzwa Forsina (Department of Public Health and Family Medicine, 2023)
Community participation is an effective strategy for strengthening health systems and progressively realising health rights. For meaningful community participation to occur, the capacity of formal or informal community organisations and mechanisms involved in addressing social determinants of health needs to be strengthened. One way of doing this is through training. There is minimal research on the efforts of community structures set up to address social determinants of health and health needs in communities, following training to strengthen their capacity. This study sought to evaluate the successes and challenges of a particular Community Systems Strengthening Project which, between 2016 and 2019, set out to train health committee members and community health activists in Gugulethu, South Africa. In so doing, it investigated whether and how the health committee members and Community Health Activists assumed an activist role in the community and are engaging in meaningful community participation. A mixed methods evaluative study was conducted in two phases during 2020-2021. The first phase was a scoping review of available literature, followed by an evaluative study including review of project documents, observation by attending events organised by the project and other community organisations, and in-depth interviews with health committee members (2), community health activists (4) and project staff (4). The training intervention was found to have influenced the health committee members and Community Health Activists thinking, understanding and practice in their community efforts to address social determinants of health. Therefore, adequate support, training, and an enabling environment can facilitate meaningful community participation in health. Ultimately, these measures will contribute to the progressive realisation of the right to health and the right to community participation, and ultimately health system transformation. The limited adaptability of the intervention, limited resources, participant perceptions and sustainability were found to be obstacles to meaningful community participation. This dissertation consists of two parts. The study protocol, Part A, outlines the rationale of undertaking this research and the proposed methods. Part B consists of the journal ready manuscript which presents the results and discussion of the research findings.